IL-12 and Mucosal CD14+ Monocyte-Like Cells Induce IL-8 in Colonic Memory CD4+ T Cells of Patients With Ulcerative Colitis but not Crohn's Disease. (15th June 2019) - Chapuy, Laurence; Bsat, Marwa; Rubio, Manuel; Sarkizova, Sisi; Therrien, Amélie; Bouin, Mickael; Orlicka, Katarzina; Weber, Audrey; Soucy, Geneviève; Villani, Alexandra-Chloé; Sarfati, Marika
Abstract: Background and Aims: CD14 + mononuclear phagocytes [MNPs] and T cells infiltrate colon in ulcerative colitis [UC]. Here we investigated how CD14 + MNPs and the cytokines they produce shape the colonic effector T cell profile. Methods: Colonic or mesenteric lymph node [mLNs] CD4 + T cells isolated from UC or Crohn's disease [CD] patients were stimulated with cytokines or autologous CD14 + MNPs. Cytokine expression was assessed by intracytoplasmic staining and multiplex ELISA. Unsupervised phenotypic multicolour analysis of colonic CD14 + MNPs was performed using the FlowSOM algorithm. Results: Among CD14 + CD64 + HLA-DR + SIRPα + MNPs, only the pro-inflammatory cytokine-producing CD163 − subpopulation accumulated in inflamed UC colon and promoted mucosal IL-1β-dependent Th17, Th17/Th1, Th17/Th22 but not Th1 responses. Unsupervised phenotypic analysis of CD14 + CD64 + MNPs segregated CD163 − monocyte-like cells and CD163 + macrophages. Unexpectedly, IL-12, IL-1β and CD163 −, but not CD163 +, cells induced IL-8 expression in colonic CD4 + T cells, which co-expressed IFN-γ and/or IL-17 in UC and not CD. The CD163 − monocyte-like cells increased the frequency of IL-8 + IL-17 +/− IFN-γ +/− T cells through IL-1β and IL-12. Finally, colonic IL-8 + T cells co-expressing GM-CSF, TNF-α and IL-6 were detected ex vivo and, promoted by IL-12 in the mucosa and mLNs in UC only. Conclusions: Our findings established a link between monocyte-like CD163 − MNPs, IL-12, IL-1β and the detection of colonic memory IL-8-producing CD4 + T cells, which might all contribute to the pathogenesis of UC.